Night Cooled Radiant Cooling Panel for Sustainable Building Cooling Mode in Malaysia - Baharun, Azhaili; Imran, Muhammad Syukri; Ibrahim, Siti Halipah; Abidin, Wan Azlan Wan Zainal (Penerbit Universiti Sains Malaysia, 2018)
Night air temperature in Malaysia is generally about 23°C and is a potential source of heat sink to dissipate heat gain from a building. A thermal storage tank was used to store a certain quantity of water and was passively cooled during the night using the pitched roof as a heat exchanger to chill the water to as low as 22°C. The free cooling of water was then used as a cooling medium to cool the modular radiant cooling panel during the day time when the outdoor temperature exceeds 30°C. The experiment shows that the system was able to maintain an indoor temperature of less than 28°C when the outdoor temperature peaked to nearly 34°C while providing acceptable thermal comfort with certain controlled air movement. The use of the hydronic radiant cooling panel with free night cooled water as its coolant is proven to have signifcant energy saving potential of up to 85% while at the same time provide an acceptable room thermal comfort which meets the international standard criteria such as the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE) Standard 55.